Determination of the high molecular weight β-glucan content of malt wort by a spectrophotometric method – determination of the accuracy, repeatability and reproducibility: Submitted on behalf of the EBC Analysis Committee - Freijee, F. J. M. (BrewingScience, 2005)
A new spectrophotometric method for the determination of the soluble high molecular weight mixed linkage (1,3)(1,4) β-D glucan (β-glucans) fraction present in malt was collaboratively tested by the Analysis Committee of the European Brewery Convention according to ISO Standard 5725-2 in order to determine its suitability for publication in Analytica-EBC. At the same time and by using the same samples the fluorimetric method used currently was also collaboratively tested. Accuracy, repeatability r(95) and reproducibility R(95) values are presented. The new spectrophotometric and the fluorimetric method in current use were found to have comparable and acceptable within and between laboratory precision for the determination of β-glucans. For the new spectrophotometric method, repeatability r(95) and reproducibility R(95) were found to be independent of the mean value and were 28,2 mg/l and 59,4 mg/l respectively over the range of β-glucan tested (88 to 308 mg/l). The new spectrophotometric method using a β-glucan assay kit from NovaBiotec® Dr. Fechter GmbH, Berlin, Germany, is recommended for inclusion in Analytica-EBC (Method 4.16.3).